Effect of Leaflet-Based Counseling on Knowledge and Attitudes Toward Iron Tablet Use Among Pregnant Women in West Aceh, Indonesia - Wahyu, Yudha Ramadhar; Junita, Dini (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
The Indonesian government has implemented various efforts to reduce anemia among pregnant women, including the provision of 90 iron supplement tablets (Tablet Tambah Darah, TTD) during pregnancy. Counseling is one of the strategies used to improve maternal knowledge and awareness regarding the importance of iron tablet consumption. This study aimed to determine the effect of leaflet-based counseling on pregnant women’s knowledge and attitudes toward iron tablet consumption at the Seuneubok Village Health Center, Johan Pahlawan Subdistrict, West Aceh Regency. This quantitative study employed a quasi-experimental design. A total sample of 23 pregnant women was selected using purposive sampling. The study was conducted in Seuneubok Village in October 2023. Knowledge and attitude data were collected using questionnaires, and data analysis was performed using a paired t-test. The average knowledge score increased by 9.0 points from pretest to posttest, while the average attitude score increased by 7.26 points. The results showed a significant difference in both knowledge and attitudes before and after the intervention (p = 0.000 for both outcomes). These findings indicate that counseling using leaflets effectively improves knowledge and attitudes regarding iron supplement tablet (TTD) consumption among pregnant women at the Seuneubok Village Health Center.